2018
DOI: 10.1186/s13662-018-1535-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stability and Hopf bifurcation in a fractional Gauss-type predator–prey model with Allee effect and Holling type-III functional response

Abstract: The Kolmogorov model has been applied to many biological and environmental problems. We are particularly interested in one of its variants, that is, a Gauss-type predator-prey model that includes the Allee effect and Holling type-III functional response. Instead of using classic first order differential equations to formulate the model, fractional order differential equations are utilized. The existence and uniqueness of a nonnegative solution as well as the conditions for the existence of equilibrium points a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…The Hopf bifurcation is a local phenomenon when a stable equilibrium point loses its stability and all nearby solutions converge to a periodic solution namely limit-cycle if a parameter is varied [54,60,61]. It is shown that many fractional-order models involving the Caputo operator undergo a Hopf bifurcation which is driven by the order of the derivative (see [2,17,34,53,62]).…”
Section: The Existence Of Hopf Bifurcationmentioning
confidence: 99%
“…The Hopf bifurcation is a local phenomenon when a stable equilibrium point loses its stability and all nearby solutions converge to a periodic solution namely limit-cycle if a parameter is varied [54,60,61]. It is shown that many fractional-order models involving the Caputo operator undergo a Hopf bifurcation which is driven by the order of the derivative (see [2,17,34,53,62]).…”
Section: The Existence Of Hopf Bifurcationmentioning
confidence: 99%
“…Definition 3.2 25,26 We say that U * is an equilibrium point of system (3.1) if and only if h(t, U * ) = 0. Lemma 3.1 26,27 Let J(U * ) be the Jacobian matrix of model (3.1) near U * and λ…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…, then the equilibrium point U * is a saddle point. Lemma 3.2 26,27 Let U * , J(U * ) be equilibrium point, Jacobian matrix of system (3.1), respectively, and λ i be the eigenvalues of Jacobian matrix J(U * ) of system (2.1).…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…We discuss existence,uniqueness and stability of the order-1 periodic orbit of system (3) based on the qualitative analysis of system (1).…”
Section: Dynamic Properties Of the Control Systemmentioning
confidence: 99%
“…The Allee effect is a phenomenon in biology characterized by a correlation between population size or density and the mean individual fitness (often measured as per capita population growth rate) of a population or species [11,15,17]. Many scholars investigated the rich dynamical behaviours of predator-prey model with Allee effect [1,7,16,18,21,24,34,40,44,45,48]. To consider that the predators are difficult to seek spouses when the species has a low population density, the Allee effect on predator is introduced to model phenomenon.…”
Section: Introductionmentioning
confidence: 99%